2015
DOI: 10.1111/cei.12738
|View full text |Cite
|
Sign up to set email alerts
|

The CD68+/H-ferritin+ cells colonize the lymph nodes of the patients with adult onset Still's disease and are associated with increased extracellular level of H-ferritin in the same tissue: correlation with disease severity and implication for pathogenesis

Abstract: Summary In this work, we aimed to evaluate the levels of ferritin enriched in H subunits (H‐ferritin) and ferritin enriched in L subunits (L‐ferritin) and the cells expressing these two molecules in the lymph node (LN) biopsies obtained from adult‐onset Still's disease (AOSD) patients, and the possible correlation among these data and the severity of the disease. Ten patients with AOSD underwent LN biopsy. All the samples were stained by immunofluorescence. A statistical analysis was performed to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…This result may confirm previous reports showing that the persistence of skin lesions correlates with the degree of systemic activity, and although the majority of papers discussing these persistent AOSD‐related skin lesions are case reports or small series, some authors found a significant correlation of AOSD activity with a poor outcome . With regard to the increased H‐ferritin expression in skin lesions, we found a strong correlation between this expression and a more severe disease, paralleling previous studies regarding different target organs of AOSD .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result may confirm previous reports showing that the persistence of skin lesions correlates with the degree of systemic activity, and although the majority of papers discussing these persistent AOSD‐related skin lesions are case reports or small series, some authors found a significant correlation of AOSD activity with a poor outcome . With regard to the increased H‐ferritin expression in skin lesions, we found a strong correlation between this expression and a more severe disease, paralleling previous studies regarding different target organs of AOSD .…”
Section: Discussionsupporting
confidence: 92%
“…These results might suggest that ferritin up-regulation, under the influence of proinflammatory cytokines such as IL-1b, IFN-g and TNF, which we found expressed largely in the skin of our patients, might further induce the Hferritin expression which, amplifying the production of proinflammatory cytokines, thus generating a vicious loop which perpetuates the inflammatory state [12][13][14][15][34][35][36][37]. Of interest, we observed a significant increase of tissue levels of IL-1b which co-localize with H-ferritin, confirming the pivotal role of IL-1b during this disease [12][13][14][15].…”
Section: Discussionmentioning
confidence: 74%
“…Further, 60–80% of AOSD patients experience a macular or maculopapular evanescent salmon-pink skin rash associated with the fever spiking [3841]; some patients, those with a usually more severe outcome, may experience this skin involvement for many weeks [7, 42]. Similar to previous studies [22, 24], a strong increase of inflammatory markers as well as of serum ferritin levels were observed herein [43, 44], confirming the systemic nature of the disease. Although it has been proposed that AOSD might be included within the so called “Hyperferritinemic Syndrome”, a common umbrella gathering different diseases in which the increased circulating ferritin levels might not only reflect an acute phase response but be directly involved in inflammation [25], our study did not find any correlation between the levels of this molecule and the patient outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…To date, H‐ferritin and CD68 + /H‐ferritin + cells were correlated significantly with haematological involvement, serum ferritin and CRP of our MAS patients. These results suggest potentially new biomarkers evaluating severity of the MAS clinical picture, possibly improving outcome in these patients . In fact, diagnosis and appropriate treatments may be delayed, due to non‐specific findings in the early phases of disease, thus new biomarkers may improve the management of this life‐threating syndrome .…”
Section: Discussionmentioning
confidence: 98%